Outcomes beyond the Third Month of Anticoagulation in Patients Aged >75 Years with a First Episode of Unprovoked Venous Thromboembolism - Iñurrieta, Amaia; Pedrajas, José María; Núñez, Manuel Jesús; López-Jiménez, Luciano; Velo-García, Alba; García, Juan Carlos; Lecumberri, Ramón; Jiménez, David; Pons, Isaac; Monreal, Manuel; the RIETE Investigators (TH Open, 2018)
Background The ideal duration of anticoagulant therapy in elderly patients with unprovoked venous thromboembolism (VTE) has not been consistently evaluated.Methods We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) registry to compare the rate and severity of pulmonary embolism (PE) recurrences versus major bleeding beyond the third month of anticoagulation in patients >75 years with a first episode of unprovoked VTE.Results As of September 2017, 7,830 patients were recruited: 5,058 (65%) presented with PE and 2,772 with proximal deep vein thrombosis (DVT). During anticoagulant therapy beyond the third month (median, 113 days), 44 patients developed PE recurrences, 36 developed DVT recurrences, 101 had major bleeding, and 241 died (3 died of recurrent PE and 19 of bleeding). The rate of major bleeding was twofold higher than the rate of PE recurrences (2.05 [95% confidence interval, CI: 1.68–2.48] vs. 0.90 [95% CI: 0.66–1.19] events per 100 patient-years) and the rate of fatal bleeding exceeded the rate of fatal PE events (0.38 [95% CI: 0.24–0.58] vs. 0.06 [95% CI: 0.02–0.16] deaths per 100 patient-years). On multivariable analysis, patients who had bled during the first 3 months (hazard ratio [HR]: 4.32; 95% CI: 1.58–11.8) or with anemia at baseline (HR: 1.87; 95% CI: 1.24–2.81) were at increased risk for bleeding beyond the third month. Patients initially presenting with PE were at increased risk for PE recurrences (HR: 3.60; 95% CI: 1.28–10.1).Conclusion Prolonging anticoagulation beyond the third month was associated with more bleeds than PE recurrences. Prior bleeding, anemia, and initial VTE presentation may help decide when to stop therapy.
Keywords: venous thromboembolism; age; anticoagulant therapy; hemorrhage; mortality